Assessing the Integration of Solar Process Heat in the Dairy Industry: A Case Study in Chile - Pailahueque-Barahona, N (Elsevier Ltd, 2024)
Solar heat for industrial processes (SHIP) in the dairy industry has attracted considerable interest during the last few years. The present study assesses the use of solar heat in dairy factories applying Ultra High Temperature pasteurization, using three locations in Chilean central and southern regions as case studies. The analysis utilizes numerical simulations considering annual energy performance, economic feasibility, size of thermal energy storage (TES), and the economic competitiveness for four different solar thermal collector technologies: Flat Plate Collector (FPC), Evacuated Tube Collector, Parabolic Trough Collector (PTC), and Linear Fresnel Reflector. The numerical simulations were conducted using the TRNSYS software for varying meteorological parameters and hourly heat load profile. The integration scheme selected for the implementation of the SHIP systems considers supply level to reheat the boiler s feedwater. The results show that the minimum levelized cost of heat ranges between 78 USD/MWh – 79 USD/MWh, with FPC and PTC showing the lower values. For all the companies analyzed, the minimums values of LCoH were observed when considering specific storage volumes between 75 l/m2–120 l/m2, indicating a strong relationship between solar resource availability and financial performance. © 2024 Elsevier Ltd